2020
DOI: 10.18597/rcog.3594
|View full text |Cite
|
Sign up to set email alerts
|

Frecuencia y causas de suspensión de cirugías ginecológicas y satisfacción de las pacientes: Hospital III ESSALUD, Lima, Perú

Abstract: Objetivo: describir la frecuencia de la cancelación de cirugía ginecológica, así como los factores causantes de esta suspensión y hacer una aproximación a la percepción de los pacientes ante esta situación. Materiales y métodos: serie de casos en la que se incluyeron pacientes de 18 años o más programadas para cirugía ginecológica por patología benigna, a quienes les fue cancelada la cirugía, en un hospital general de referencia, ubicado en Lima, Perú, entre junio de 2019 y marzo de 2020. Se evaluaron las cara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…12 In Peru, a study detected the main factor for gynecological surgeries cancellation were medical issues in 46.5%; administrative issues in 36.6%, mainly due to lack of operating room time in 25.4%. 13 Likewise, another study conducted in Peru in 2016 showed that the causes of suspension of surgeries according to patient institutional status, are patient-related causes. 14 A study carried out in Cali, Colombia, found that 70.91% of surgery cancellations in a level III clinic were attributed to patient-related causes, 12.73% to administrative causes, 12.73% to causes related to the pandemic and 3.64% due to causes related to the specialist.…”
Section: Discussionmentioning
confidence: 99%
“…12 In Peru, a study detected the main factor for gynecological surgeries cancellation were medical issues in 46.5%; administrative issues in 36.6%, mainly due to lack of operating room time in 25.4%. 13 Likewise, another study conducted in Peru in 2016 showed that the causes of suspension of surgeries according to patient institutional status, are patient-related causes. 14 A study carried out in Cali, Colombia, found that 70.91% of surgery cancellations in a level III clinic were attributed to patient-related causes, 12.73% to administrative causes, 12.73% to causes related to the pandemic and 3.64% due to causes related to the specialist.…”
Section: Discussionmentioning
confidence: 99%